Are circadian rhythms new pathways to understand Autism Spectrum Disorder?. Issue 4 (November 2016) - Geoffray, M-M.; Nicolas, A.; Speranza, M.; Georgieff, N.
Highlights: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder. Circadian rhythms are a complex biological timing system. Circadian rhythms are involved in brain development. ASD could be related to circadian rhythm disorders at critical brain developmental periods. Abstract: Autism Spectrum Disorder (ASD) is a frequent neurodevelopmental disorder. ASD is probably the result of intricate interactions between genes and environment altering progressively the development of brain structures and functions. Circadian rhythms are a complex intrinsic timing system composed of almost as many clocks as there are body cells. They regulate a variety of physiological and behavioral processes such as the sleep-wake rhythm. ASD is often associated with sleep disorders and low levels of melatonin. This first point raises the hypothesis that circadian rhythms could have an implication in ASD etiology. Moreover, circadian rhythms are generated by auto-regulatory genetic feedback loops, driven by transcription factors CLOCK and BMAL1, who drive transcription daily patterns of a wide number of clock-controlled genes (CCGs) in different cellular contexts across tissues. Among these, are some CCGs coding for synapses molecules associated to ASD susceptibility. Furthermore, evidence emerges about circadian rhythms control of time brain development processes.